Efficient use and development prospects of alternative energy sources in Kazakhstan. - Tulemetova, A. S.; Polezhayeva, I. S.; Yessirkepova, A. M. (Journal of Economic Research & Business Administration, 2015)
The goal of the research is the analysis of comparative indicators of power plants, and also identification of methods of effective use and prospects of development of nonconventional power sources in the Republic of Kazakhstan. Methodology of the research. Research was constructed on the following general scientif-ic methods: abstract-logical, calculation – constructive, forecasting and method of generalization. The main value of the work is offers and recommendations following from the results of research which are submitted on increase of scales of production and usage of renewable sources of energy and carrying out policy of energy saving. Results of the research are the priority directions on application of renewable sources of energy and carrying out policy of energy saving.